Characterization of the poetics of animated film - Esparza Santa María, Luis Ángel (2021)
The writing of a screenplay for an animated film for children is a delicate process due to several factors: the nature of a script, whose goal is not only to be written, but must also be produced to fulfill its purpose; the high costs of audiovisual production, which oblige it to include commercial values in its poetics to guarantee a recovery of the large investment; the demands of a highly segmented public, such as children; and the demands of a society that expects high commercial values from cultural industries. In this sense, the main goal of this article is to propose a characterization of children’s animation cinema based on three axes: the commercial (in order to meet the audience’s requirements), the authorial (in order to respect the author’s poetics) and the hybrid (which balances both interests). To achieve this, a theoretical framework oriented to mass culture based on Mario Vargas Llosa and Umberto Eco has been established. Additionally, Robert McKee has been consulted as the theorist of the audiovisual script. On this basis, a characterization of children’s animation cinema has been proposed that, after analyzing and describing some examples, yields as a result great variety in the subject matter and style of authorial cinema, which makes this axis very personal and free; and obvious similarities in commercial cinema, which make this axis easily categorized, and therefore adaptable to a hybrid proposal of animated cinema. The main conclusion is that a categorization like this is necessary to create a hybrid proposal for children’s animated cinema, necessary in a still nascent industry.